The Natural Way to Draw : a working plan for art study - Nicolaides, Kimon, 1892-1938. (Boston : Houghton Mifflin Company, 1941)
This classic book offers a comprehensive lesson in drawing the natural form. Split into sixty-four easy exercises including 'Gesture Drawing', 'Group Poses' and 'Study of the Bones', this book is great for anyone wishing to learn how to draw. Many of the earliest books, particularly those dating back to the 1900s and before, are now extremely scarce and increasingly expensive.
Contour and gesture -- The comprehension of gesture -- Weight and the modelled drawing -- Memory drawing and other quick studies -- The modelled drawing in ink-the daily composition -- The modelled drawing in water color-right-angle study -- Emphasis on contour-the head -- Special form studies -- An approach to the subject of technique -- The simple proportions-effort -- The study of drapery -- The figure with drapery-the subjective impulse -- The sustained study -- Light and shade -- An approach to the study of anatomy -- The long composition -- Exercises in black and white crayon -- Studies of structure -- Analysis through design -- Study from reproduction -- The muscles -- Exercises in black and white oil color -- Analysis through design-continued -- The subjective element -- An approach to the use of color.
Keywords: Drawing -- Study and teaching; Nonfiction